2016
DOI: 10.1136/annrheumdis-2016-210131
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial DNA haplogroups influence the risk of incident knee osteoarthritis in OAI and CHECK cohorts. A meta-analysis and functional study

Abstract: Objective To evaluate the influence of the mitochondrial DNA (mtDNA) haplogroups in the risk of incident knee osteoarthritis (OA) and to explain the functional consequences of this association to identify potential diagnostic biomarkers and therapeutic targets. Methods Two prospective cohorts contributed participants. The osteoarthritis initiative (OAI) included 2579 subjects of the incidence subcohort, and the cohort hip and cohort knee (CHECK) included 635, both with 8-year follow-up. The analysis included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 50 publications
5
67
1
1
Order By: Relevance
“…In the presence of staurosporine, which induces cell apoptosis, the cybrids with the haplogroup H had over 50% more apoptotic cells than the cybrids with the low OA risk haplogroup J 7. These data, therefore, prove the functional relevance of mtDNA variation linked to risk of OA on cell function and survival and is in agreement with recent work by the same group showing that OA cartilage exhibits signs of early molecular ageing compared with healthy age-matched cartilage 2…”
Section: Functional Analysis Of Mtdna Variantssupporting
confidence: 91%
See 2 more Smart Citations
“…In the presence of staurosporine, which induces cell apoptosis, the cybrids with the haplogroup H had over 50% more apoptotic cells than the cybrids with the low OA risk haplogroup J 7. These data, therefore, prove the functional relevance of mtDNA variation linked to risk of OA on cell function and survival and is in agreement with recent work by the same group showing that OA cartilage exhibits signs of early molecular ageing compared with healthy age-matched cartilage 2…”
Section: Functional Analysis Of Mtdna Variantssupporting
confidence: 91%
“…The mtDNA haplotypes T, J and the JT cluster, on the other hand, are significantly associated in populations from the USA, the Netherlands and Spain with radiographic incidence and progression of the disease7 15 (table 1). Fernandez-Moreno and coauthors report that the mtDNA haplogroup J, the same haplogroup associated with lower OA prevalence, lower disease progression and lower cartilage loss, is also associated with a significantly lower risk of incident knee OA in a population of 3124 individuals from two prospective cohorts from the Netherlands and the USA 7…”
Section: Mtdna In Oamentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between mtDNA haplogroups and apoptosis is not a new discovery; a study by Kenney et al showed that cybrids with haplogroup J had reduced expression of apoptosis‐related genes compared to cybrids with haplogroup H . In addition, cybrids with haplogroup J also show a lower grade of apoptosis under stress conditions as well as a lower expression of the apoptotic gene BBC3 than cybrids with haplogroup H . Taken together, these findings indicate that inherited mitochondrial variants can affect apoptosis pathways and, since chondrocyte death is a central feature in OA progression , this could explain, at least in part, the associations of haplogroup J with a lower rate of knee and hip OA prevalence and incident knee OA .…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, the mtDNA haplogroups influence the prevalence of OA in different geographic populations and have been shown to affect radiographic progression and cartilage integrity over time in patients in the progression subcohort of the Osteoarthritis Initiative . A recent meta‐analysis involving >3,000 subjects concluded that mtDNA haplogroups significantly influence the rate of incident knee OA; specifically, those subjects harboring haplogroup J had a significantly decreased risk of developing incident knee OA at 8 years compared to subjects harboring haplogroup H, which differs in terms of reactive oxygen species and ATP production, mitochondrial metabolism, and apoptosis .…”
Section: Introductionmentioning
confidence: 99%